Insulin detemir may be less efficacious in patients with nonalcoholic fatty liver disease and hypertriglyceridemia. Issue 1 (1st December 2015) - Whyte, Martin; Quaglia, Alberto; Hopkins, David
Key Clinical Message: Insulin detemir is commonly used in obese patients with diabetes mellitus as it is considered hepatoselective and causes less weight gain. We describe a relative lack of effectiveness of detemir in patients with significant NAFLD and hypertriglyceridemia, compared to isophane insulin. This may affect how such patients are managed with insulin. Abstract : Insulin detemir is commonly used in obese patients with diabetes mellitus as it is considered hepatoselective and causes less weight gain. We describe a relative lack of effectiveness of detemir in patients with significant NAFLD and hypertriglyceridemia, compared to isophane insulin. This may affect how such patients are managed with insulin.